Development of Digital Storytelling-Based Science Teaching Materials to Improve Students’ Metacognitive Ability - Dewi, N. R.; Kannapiran, S.; Wibowo, S. W. A. (Jurnal Pendidikan IPA Indonesia, 2018)
This study aims to produce digital-based storytelling teaching materials of natural science that can facilitate the students to be able to explore the object of science learning deeply and to improve their metacognitive ability. This research is development research. The samples used are four teachers and 40 junior high school students. The technique of gathering data employed a testing method, documentation study, and questionnaire. Validation is done to determine the feasibility of teaching materials. The research result of the improvement of students’ metacognitive ability is measured by using the testing method in the form of pretest and posttest. Pretest and posttest data were analyzed by N-gain and t-test of significance. The result of the research shows that the average percentage of validation result of media expert and material expert is 97,70% and 95,16%. According to experts, all developed products are very feasible to use. The results of metacognitive enhancement (N-gain) for levels 1 to 5 respectively were 0.36; 0.56; 0.49; 0.45 and 0.39. The results of significance test showed that the t-count 7.65 and t-table of 2.03 which that the mean improvement of the metacognitive ability of students is significant. Based on the results of this study, it can be concluded that the teaching materials based on digital storytelling are feasible to be used to improve students’ metacognitive ability.